Training Treatment Skill of Children Abuse Victims for College Students - Koesdyantho, Agustinus Roedy (International Journal of Community Service Learning, 2021)
Child abuse is a serious phenomenon that needs treatment to recover the victims. The problems occurred are the students are lack of understanding in giving treatments for child abuse victims, and they have no experience and skills in giving treatment to child as abuse victims. The present article aims at describing a training of giving treatments to recover children as victims from abuse and violence to show the students’ (participants) knowledge and service before they do internship program at an orphanage in order to have knowledge and skills to give treatments for child abuse victims. The type of research is descriptive qualitative. The subject of research is 7th semester students of guidance and counseling, Indonesia. The methods in collecting the data used observation and a questionnaire. In analyzing the data, the researcher used interactive analysis that covers data display, data reduction, and conclusion drawing. The result of the research are the improvements of the college students’ knowledge and service in giving treatment for child abuse victims; they are familiar with six forms of treatment to recover the victims that consist of Combined Parent-Child Cognitive Behavioral Therapy (CPC-CBT), Parent Training and Multi-systemic Therapy, Project Support (Children’s Protective Services), Web-based parenting skills, Home Visiting Program, and School Based Mental Health Intervention for Children. So, are treatments in the form of collaboration between parents (caregivers), schools, and children (as victims) to recover child abuse and violence through a variety of phases to realize the purposes and children abuse as victims need appropriate treatment based on the condition of them and such six treatments as a choice and solution to recover the victims. The research is that the improvement of knowledge and skills of the students to give treatment for children as abuse victims.